Perlindungan Hukum terhadap Anak Sebagai Korban Tindak Pidana Cyberbullying - Alinda Julietha Adnan; Dewi Putriyani; Hycal Asmara Wibowo; Suta Ramadan (Universitas Muhammadiyah Yogyakarta, 2024)
The development of misused information technology has resulted in the emergence of modern crimes such as cyberbullying, which uses the internet as a means of carrying it out. Lack of supervision in the family, school, community and individual environment causes cyberbullying to occur. This research aims to investigate legal protection for children who are victims of cyberbullying and identify mechanisms for dealing with cyberbullying against children. The research method applied uses a normative juridical approach. Child protection in cases of cyberbullying is normatively regulated in Article 29 of Law of the Republic of Indonesia Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE). The mechanism for dealing with cyberbullying against children can be done through preventive and preemptive efforts